Psychological Health Before, During, and After an Economic Crisis : Results from Indonesia, 1993–2000 - Thomas, Duncan; Friedman, Jed (World Bank, 2012)
The 1997 Indonesian financial crisis resulted in severe economic dislocation and political upheaval. Previous studies have established the detrimental consequences for economic welfare, physical health, and child education. The crisis also affected the psychological well-being of the Indonesian people. Comparing responses of the same individuals interviewed before and after the crisis, this study documents substantial increases in several dimensions of psychological distress among men and women across the age distribution. It shows larger impacts of the economic crisis on the more vulnerable groups, including those with low education, the rural landless, urban residents, and those in provinces most affected by the crisis. Elevated psychological distress persists even after the economy returns to precrisis levels, suggesting that the deleterious effects of the crisis may persist longer on the psychological well-being of the Indonesian population than on standard measures of economic well-being.